A procedural review on khalwat ops / Dazrin Mohd Darbi, Shahrul Radzlin Mohd Idris and Collin Babat - Mohd Darbi, Dazrin; Mohd Idris, Shahrul Radzlin; Babat, Collin (2007)
This thesis deals with the law on khalwat in Malaysia. It deals with the ground procedures in its enforcement by the State religious department as well as its officers. The main aim of this research is to examine the procedures and to highlight the procedural irregularities in light of the constitutional right and liberties of a person being held for the offence ofkhalwat under the Syariah Law. The enforcement of khalwat law violates the fundamental rights of the individual as provided under our Constitution and recognized under international standards thus critical reevaluation of the law is necessary. We shall attempt to examine the written and unwritten procedures and code of conduct in of the religious enforcers in enforcing khalwat law. We will determine whether procedures such as spying, intentional fault finding, breaking and entering into a premise without a warrant and others are constitutional or not. In light of the above we shall highlight the flaws in the current system and will attempt to provide suggestions and recommendations so as to balance out the need to enforce the law and the rights of the individual. In our research we will also look into the law of khalwat in today's modern context and determine whether such laws are still necessary.